Gimnástica del Bello Sexo [Gymnastics for the Fairer Sex]: A Vanguard Approach to Female Physical and Moral Education in Hispanic America (1827) - Huidobro, Gabriela; Briones, Daniel (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2025)
This article examines Gimnástica del Bello Sexo o Ensayos sobre la Educación Física de las Jóvenes (London, 1827), an early manual on women’s physical and moral education in Hispanic America. Framed within Enlightenment and early republican thought, the work negotiates traditional gender ideals with emerging liberal ideas about female education. Through moderate and playful activities—such as walking, swinging, and singing—it promotes physical exercise as both moral training and a health practice. The analysis shows how the text reinforced feminine virtues of grace, beauty, and modesty while subtly opening space for women’s participation in educational and civic life. Gimnástica del Bello Sexo thus stands as a pioneering source in the history of female physical education in Hispanic America, anticipating later institutional developments and reflecting the cultural redefinition of femininity during a time of political and social transformation.